Validity and reliability of different techniques of neck–shaft angle measurement. Issue 11 (November 2018) - Bizdikian, A.J.; Assi, A.; Bakouny, Z.; Yared, F.; Saghbini, E.; Bakhos, G.E.; Esber, S.; Khalil, N.; Otayek, J.; Ghanimeh, J.; Sauret, C.; Skalli, W.; et al.
Abstract : Aim: To determine a valid and reliable neck–shaft angle (NSA) measurement method while rotating the pelvises in increments of 5° in order to simulate patient malpositioning. Materials and methods: CT images of 17 patients were used to produce digitally reconstructed radiographs in frontal and lateral views and three-dimensional (3D)-reconstructions of the femurs, considered to be the reference standard. Malpositioning was simulated by axially rotating the frontal radiographs from 0° to 20°. Three operators measured in two-dimensions the NSA using four different methods, three times each, at each axial rotation (AR) position. Method 1 (femoral neck axis drawn by joining the centre of the femoral head (CFH) to the median of the femoral neck base; femoral diaphysis axis drawn by joining the median of two lines passing through the medial and lateral edges of the femoral axis below the lesser trochanter) and method 2 (femoral axis taken as the median of a triangle passing through base of femoral neck and medial and lateral head–neck junction; femoral diaphysis as previous) were described for the first time; method 3 was based on a previous study; method 4 was a free-hand technique. Reliability, validity, and global uncertainty were assessed. Results: Method 1 showed the best reliability and validity. The global uncertainty also showed minimal values for method 1, ranging from 7.4° to 14.3° across AR positions. Conclusion: Method 1, based on locating the CFH, was the most reliable and valid method and should be considered as a standardised two-dimensional NSA measurement method for clinical application. Highlights: No consensus exists on the best method to measure the neck-shaft angle (NSA). Measurement of NSA depends on the correct positioning of the patient. CT scans and digitally reconstructed radiographs with 3D reconstructions were used. 4 methods of NSA measurement were tested for reliability and validity. Locating the femoral head centre is the most valid and reliable method.